Liderazgo de enfermería para la correcta implementación de estrategias de calidad y seguridad del paciente en hospitales de América Latina: scoping review - Valladolid Jumbo, Vanessa Gabriela (2025)
Nursing leadership is a key factor for hospital management in the implementation of quality and patient safety strategies, especially in Latin America due to its social, structural, and organizational challenges. The objective of this research is to analyze and map the existing literature on nursing leadership and its influence on the successful implementation of quality and patient safety strategies in Latin American hospitals. This research approach is qualitative with descriptive quantitative elements, based on a scoping review and supported in the context of a secondary study: Scoping Review, following the Joanna Briggs Institute (JBI) methodology, using the Evidence Based Nursing (EBN) methodology as a framework, following the PRISMA-ScR extension. The search was conducted in PubMed, VHL, Google Scholar, and complementary sources, considering articles published in English, Spanish, and Portuguese between 2014 and 2024. The inclusion criteria considered primary and secondary research, gray literature, and university theses, while the exclusion criteria considered documents without full access, unrelated to leadership, and not included in the regional competition. Ultimately, 22 studies were selected and classified into four main themes: 1) Nursing leadership styles; 2) Impact of leadership on quality of care and patient safety; 3) Successful nursing leadership strategies for patient safety; and 4) Leadership characteristics in the Latin American hospital context. Positive results were demonstrated regarding the relationship between transformational leadership and nursing practice, leading to process improvement, a reduction in adverse events, and a greater culture of patient safety. Therefore, nursing leadership is conceived as a strategy to consolidate changes in hospital services in Latin America and represents a need to strengthen leadership skills through public policies and continuing education that position nurses as key factors in quality and patient safety.